Media Landscape Subculture in the Society 5.0: Case Study on Indonesia Urban Toys Scene - Rani Chandra Oktaviani; Donna Asteria; Niken Febrina Ernungtyas (Nyimak: Journal of Communication, 2026)
This research examines the development of digital media, which has significantly changed the media landscape in subcultural groups. This study identifies a gap in research rarely discussed by communication experts, who typically focus more on maps and logic of mainstream media or popular culture, with less attention to subcultural groups. This serves as the background to the research problem, which focuses on observing the subcultural media map. Existence of subcultures, although underground, but they are developing massively in using various media. The subcultural scene that is currently a conversation phenomenon in the online world and chosen as multiple-case study is the Indonesian Urban Toys scene. The objectives of this study are: 1) Mapping media landscape among the Urban Toys subculture. 2) To determine the interaction patterns of subcultural members in the use of various media. 3) To examine the implications of the media landscape. This research using the Digital Difussion Subcultural Theory and methodology used is qualitative. The results has showen: 1) Lanscape media subcultural has 4 layers. 2) Interaction patterns are changing, blending with parent culture, pop culture, and mass culture. 3) The implications of using a variety of digital media can add value to subcultural development or even erode authentic subcultural values, when the artists concept must meet with commercial negotiations.Keywords: Digital, subculture, media, urban toys, sceneÂ ABSTRAKPenelitian ini mengkaji perkembangan media digital cukup merubah lanskap media yang digunakan oleh kalangan subkultural. Penelitian ini melihat celah kajian yang sedikit dibahas oleh pakar komunikasi, dimana biasanya mereka lebih banyak melihat pada peta dan logika media meanstream atau budaya popular, sedikit atensi pada kelompok subkultural. Hal ini menjadi latarbelakang permasalahan penelitian yang berfokus mengamati peta media subkultural. Hal ini juga ditandai adanya subkultural meskipun bersifat bawah tanah namun mereka berkembang massif dalam menggunakan media digital. Skena subkultural yang saat ini menjadi fenomena percakapan didunia daring dan dipilih menjadi objek kajian analisis multi kasus adalah skena Urban Toys Indonesia. Tujuan penelitian ini adalah: 1) Untuk memetakan lanskap media di kalangan subkultural Urban Toys. 2) Untuk mengetahui pola interaksi anggota subkultural pada penggunaan ragam media. 3) Untuk mengkaji Implikasi lanskap media subculture Urban Toys. Penelitian ini membawa Teori Digital Difussion Subkultural. Methodology penelitian yang digunakan kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukan: 1) Lanskap media subkultural memiliki 4 lapisan, yang setiap lapisanya menggambarkan nilai dan rasa subkultural yang berbeda. 2) Pola interaksi dikalangan subkultural Urban Toys mengalami perubahan, dapat bebaur dengan parent culture, pop culture dan mass culture. 3) Implikasi penggunaan ragam media digital dapat memberi nilai tambah perkembangan subkultural atau bahkan melunturkan nilai otentik subcultural yakni pada gagasan artis harus bertemu dengan dengan negosiasi komersil.Kata Kunci: Digital, subkultural, media, urban toys, skena